Gamified Assessment Supported by a Dynamic 3D Collaborative Game - Mavridis, Apostolos; Tsiatsos, Thrasyvoulos; Chatzakis, Michalis; Kitsikoudis, Konstantinos; Lazarou, Efthymios (International journal of game-based learning, 2015)
This study examined whether a 3D collaborative gave can be used as a midterm examination method and investigated the impact of this game on students' attitude towards collaboration. A total of 89 students and one coordinating professor participated in this study. The intervention lasted five weeks and took place in a computer science department. The game that was used as a treatment was dynamic and therefore the educator was able to customize its content for the examinations using an administration panel. A mixed method of quantitative and qualitative data collection was used. The results indicated that there was a statistically significant correlation between the performance of the students on the game and their performance on the final paper-based examination. However, there was no statistically significant difference between the attitude of the students towards collaboration before and after the use of the game.